Monitoring Chilean native forest area: a pending challenge - Miranda, Alejandro; Lara, Antonio; Altamirano, Adison; Zamorano-Elgueta, Carlos; Hernández, H Jaime; González, Mauro E; Pauchard, Aníbal; Promis, Álvaro (BOSQUE, 2018)
Forest monitoring is important for decision making of forest management and conservation. In Chile, the forest monitoring system was initiated in 1994, which has been continued through the implementation of regional updates. This has enabled a temporal monitoring of the distribution and surface covered by native forest. However, while regional updates have reported increase in the surface covered by native forest, other studies have shown an opposite trend. Therefore, the capacity of the forest monitoring system to measure the temporal variation in forest areas was evaluated. Specifically, a review of reports and official data of the national forest monitoring system was carried out through the fulfillment of three basic criteria: i) comparability, ii) replicability and iii) quality. According to our results, the Chilean forest monitoring system does not fulfill their basic requirements because: (i) methodologies have not been consistent over time; (ii) it does not provide a baseline of land cover or forest loss that allows comparisons with changing forest area; iii) there is not adequate error estimation and how it can affect the results and analysis of monitoring. The national forest monitoring system requires a redefinition of its aims and methods, guiding them to the long term by convening different stakeholders looking for a national agreement.